Counseling Women on Smoking Relapse Prevention During Postpartum. Issue 5 (September 2016) - Feeney, Ann; Britton, Geraldine
Abstract : Abstract: Many women who quit smoking after learning they are pregnant revert back to smoking after birth of their baby. The high rate of recidivism suggests that women need education about risk of relapse and effective strategies to remain smoke free even before they are discharged from the hospital. Despite evidence that smoking cessation and relapse prevention counseling is effective during early postpartum, many nurses do not provide their patients with this important information, perhaps because they feel inadequately prepared to do so. Helping Women Stop Smoking in Pregnancy and Beyond is an education program designed to help perinatal nurses inform women of negative risks of smoking and offer women strategies to avoid the high probability of resuming smoking after birth. It includes evidence-based interventions that can be used by nurses to provide effective smoking relapse prevention counseling to women during postpartum. Abstract : Many women who quit smoking after learning they are pregnant revert back to smoking after birth of their baby. The authors describe the Helping Women Stop Smoking in Pregnancy and Beyond education program designed for perinatal nurses to help inform women of negative risks of smoking and offer women effective strategies to avoid the high probability of resuming smoking after birth.